2006
DOI: 10.1177/0021998305055543
|View full text |Cite
|
Sign up to set email alerts
|

Laminate Theory Analysis of Composites under Load in Fire

Abstract: Laminate analysis is used to model a loaded composite plate under one-sided heat flux. The input to the laminate analysis comes from a thermal/ablative model, which predicts the temperature evolution through the thickness. It also gives the profile of residual resin content, which reflects the extent of thermal damage. Relationships are proposed to enable the computation of the elastic constants and other mechanical properties as functions of temperature and resin content. The model was applied to a 12 mm thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(186 citation statements)
references
References 21 publications
(39 reference statements)
7
173
0
4
Order By: Relevance
“…The one-dimensional governing equation to calculate the temperature rise with increasing heating time (@T=@t) is expressed as [9] …”
Section: Thermomechanical Modelmentioning
confidence: 99%
“…The one-dimensional governing equation to calculate the temperature rise with increasing heating time (@T=@t) is expressed as [9] …”
Section: Thermomechanical Modelmentioning
confidence: 99%
“…In recent years, research studies [4][5][6][7][8][9] have shown that the typical relationship between a mechanical property of a polymer composite and temperature under isothermal condition (that is, constant temperature throughout the material) is generally that shown in Figure 5. Since limited data exist on individual mechanical properties, such as modulus and strength, it is assumed for convenience that all mechanical properties can be fitted to the typical mechanical property versus temperature relationship shown in Figure 5.…”
Section: Analytical Modelsmentioning
confidence: 99%
“…The authors have, on the basis of previously published research on the high temperature performance of polymer composites [4,5,6,7,8,9], selected a sigmoid curve based on a hyperbolic tangent function [4,5,6] to describe the mechanical and bond property degradation of GFRP composites. In this study, was taken to be 1.0 because, based on TGA, the resins do not experience any significant amount of decomposition until 350°C and was the average of the observed values of the property at room temperature.…”
Section: Implementation In Structural Fire Modelmentioning
confidence: 99%
“…Since the stress-strain behaviour of the FRP composites at both ambient and elevated temperature was observed to be linear-elastic to failure in direct tension coupon tests conducted by the authors [12,23] Gibson et al [24] has been used to describe the high temperature degradation of the FRP's tensile strength and tensile elastic modulus . The Gibson et al model is semi-empirical and is based on a non-linear leastsquares curve fit of data from tests performed by the authors on a specific glass/epoxy FRP strengthening system at elevated temperatures [12,23].…”
Section: Mechanical Property Models At Elevated Temperaturementioning
confidence: 99%